Mutagenic risk in epileptic patients before and after anticonvulsant therapy - Goyle, S; Maurya, A K; Kailash, S; Maheshwari, M C (Epilepsia (Copenhagen), 1987)
Therapy with anticonvulsant drugs has often been found to result in somatic chromosome aberrations in adult patients. There is also the possibility of epileptic fathers or mothers playing a role in the production of congenital malformations in their offspring. We have used the technique of sister chromatid exchange (SCE), a sensitive indicator of mutagenicity, to observe the mutagenic susceptibility in both male and female epileptic patients in different age groups prior to and after anticonvulsant therapy, and with respect to control. The frequency of SCE was significantly higher in all the age groups for treated and untreated cases compared with control. Between treated and untreated subjects in age group 26-50 years, a significantly higher SCE frequency was observed in the untreated patients (p less than 0.01). Similarly, untreated male patients showed a significantly higher SCE frequency (p less than 0.025) compared with treated male patients. Although the results of this study provide a general assessment of mutagenicity in epileptic patients that agrees with other studies and emphasizes the role of the disease in the higher occurrence of congenital malformation in their offspring, the importance of higher SCE frequency in untreated patients remains to be explained in further studies.